Effect of activation time on the pinang frond based activated carbon for remazol brilliant blue r removal - Ahmad, Mohd Azhar; Herawan, Safarudin Gazali; Yusof, Ahmad Anas (Universiti Pahang Malaysia, 2014)
Activated carbons are regularly used for dye wastewater treatment. They can be produced from various organic materials which have a high level of carbon content. In this study, Pinang frond based activated carbon (PFAC) was produced by using a physical activation process to study the effect of different activation times in the range of 1–7 hours. The optimum PFAC sample was found with an activation time of 3 hours, which gives the highest BET surface area and pore volume of 958.23 m2/g and 0.5469 mL/g, respectively. This sample shows well-developed pore structure with a high fixed carbon content of 79.74%. The removal of 87.6% of Remazol Brilliant Blue R (RBBR) was achieved for a sample with initial RBBR concentration of 50 mg/L, and 40.8% was achieved with 500 mg/L. The results indicated that the PFAC is very effective for RBBR adsorption from aqueous solution.